Engraved stone plaquettes from the North Patagonian area (Somuncurá plateau, Río Negro, Argentina) and the use of different microscopic techniques for their analysis. Issue 1 (1st January 2019) - Lynch, Virginia; Vargas Gariglio, Jorgelina; Terranova Enrique, Daniel
ABSTRACT: The aim of this paper is to present the first record of engraved stone plaquettes recovered at the Laguna Azul site (LA-P3) located in the Somuncurá plateau (Río Negro, Argentina). The stone plaquettes record is wide and varied in Argentina and especially in the North Patagonia region; however, it mostly consists of surface finds. The four plaquettes from LA-P3 are associated with Late Holocene dates ( c .1906–1756 years BP) and in this paper the authors describe their designs and motifs, as complementary studies using different microscopy techniques. LA-P3's plaquettes displayed red residues which were analysed by SEM-EDX and allowed identification of iron and titanium on their surfaces. This study contributes to the stone plaquette register of North Patagonia, and provides novel information related to their production techniques (mostly incision) and their motifs identified (non-figurative). The low frequency of similar motifs between the sets analysed allows us to propose a certain regionalization of their production.